Rancang Bangun Private Server Menggunakan Platform Proxmox dan Penerapan Zero Trust Model dengan Cloudflare - Yulianto, Bimo Tri; Quraisy, Muhamad; Daulay, Anggriyana; Daulay, Anggriyani; Sari, Ayu Puspita (Universitas Pamulang, 2023)
This implementation emphasizes using Proxmox as the primary virtualization platform combined with the Zero Trust security concept, where each access request is rigorously assessed before being permitted. Integration with Cloudflare provides an additional layer of security through features such as web application firewall (WAF), DDoS protection, and strict access control. By adopting the Zero Trust model and leveraging Cloudflare services, the server infrastructure becomes more resilient against current cyber threats. The meticulous integration between Proxmox and Cloudflare offers a high level of security at every server access point, creating a reliable and safeguarded environment for IT services.